Kewenangan Pemerintah Daerah dalam Sistem Pemungutan Pajak Bidang Industri Pariwisata di Kota Kupang - Samuel Wahyu Kabut, Andreas (Journal of Comprehensive Science, 2024)
This study aims to analyze the authority of local governments in realizing a good tax payment system in Kupang City. As well as to find out the obstacles faced by the local government in the tourism tax payment system in Kupang City. This research uses a normative method, with this writing approach collected from documents and supported by primary data, analyzed by qualitative analysis based on deductive thinking logic. The results of this study show that the current authority in the existing regional regulations, there are still flaws for officials in the Regional Revenue Agency to abuse their authority for themselves, because the system in the current regional regulations still has weaknesses. There are two obstacles at present, namely from the internal and external sides, from the internal obstacles that exist there has not been progress in terms of technology in the application of the tax payment system process in Kupang City.